INCIDENCE OF AIDS IN QUETTA AND SUBURBS - Marri, Shah Muhammad; Goraya, Asif; Ahmed, Jamil (Journal of Ayub Medical College Abbottabad, 1999)
A generalised fear of Human Immune Deficiency Syndrome (HIV) infection was created by media ad over the world including Baluchistan, Pakistan. This fear was sometimes more grave as compared to Hepatitis B virus infection which is commoner in this part of Pakistan. There were some reported cases of Acquired Immune Deficiency Syndrome (AIDS) as well in Kech, (Makuran) area. We have studied 2,466 individuals in Quetta and suburbs to determine the incidence of A IDS.